Developing an Indonesian Regulatory Framework in the Face of SEZs 5.0 - Hutauruk, Rufinus Hotmaulana; Tan, David; Situmeang, Ampuan; Disemadi, Hari Sutra (Universitas Negeri Semarang, 2023)
Numerous emerging economies have embraced Special Economic Zones (SEZs) as more than just an instrument for policymaking to encourage growth and industrial development. Today’s “SEZ 5.0,” which is based on novel digital inventions offers a gateway to economic progression. This research utilizes the normative juridical method and secondary data based on library research. This research is novel in the way that it illuminates the numerous key lessons from effective SEZ practices, such as: geographical advantage, interoperability of zone strategic plan with the overarching development plan, acknowledging the context of the industry, and harnessing comparative advantage, as well as, making sure that SEZs are “special” in contexts of a business-friendly atmosphere supported by a sound statutory and regulatory model, along with the articulation of sustainable practices and adaptability towards the volatility of the market. This research recommends key policy lessons for the Indonesian SEZ governance.